Chernobyl : a technical appraisal. (Telford for the British Nuclear Energy Society, 1987)
This text examines the effects of the Chernobyl disaster. It describes the accident sequence, the radiological consequences in the USSR, and looks at an estimation of the radiation situation in Eastern Europe following the Chernobyl accident.